Explicit and implicit effects of gaming content on social media on the behavior of young adults - Jitoku, Daisuke; Kobayashi, Nanase; Fujimoto, Yuka; Qian, Chenyu; Okuzumi, Shoko; Tei, Shisei; Matsuyoshi, Daisuke; Tamura, Takehiro; Takahashi, Hidehiko; Ueno, Takefumi; Yamada, Makiko; Fujino, Junya (Frontiers in Psychology, 2024)
Excessive gameplay can have negative effects on both mental and physical health, especially among young people. Nowadays, social media platforms are bombarding users with gaming-related content daily. Understanding the effect of this content on people's behavior is essential to gain insight into problematic gaming habits. However, this issue is yet to be studied extensively. In this study, we examined how gaming-related content on social media affects young adults explicitly and implicitly.We studied 25 healthy young adults (average age 21.5 ± 2.2) who played online games casually and asked them to report their gaming desire. We also conducted an implicit association test (IAT) to measure their implicit attitudes toward gaming-related content. We also investigated the relationship between these measures and various psychological factors, such as personality traits, self-efficacy, impulsiveness, and cognitive flexibility. The results revealed that participants had a higher explicit gaming desire when exposed to gaming-related cues on social media than neutral cues. They also had a robust positive implicit attitude toward gaming-related content on social media. Explicit gaming desire was positively correlated with neuroticism levels. Furthermore, the IAT effect was negatively correlated with self-efficacy and cognitive flexibility levels. However, there were no significant correlations between explicit gaming desire/IAT effect and impulsiveness levels. These findings suggest that gaming-related content on social media can affect young adults' behavior both explicitly and implicitly, highlighting the need for further research to prevent gaming addiction in vulnerable individuals.